Intervención del terapista respiratorio en paciente masculino de 18 años de edad con neumonía adquirida en la comunidad. - Silva Gavica, Nerea Anahi (2022)
The focus of this study is based on the intervention of the respiratory therapist in an 18-year-old male patient with community-acquired pneumonia. Community-acquired pneumonia is one of the main lung diseases affecting older adults and children around the world. This pathology is mainly caused by the bacteria Streptococcus pneumoniae. This pathology commonly lasts a few days or even weeks, so it must be diagnosed quickly in order to administer a treatment that helps improve the signs and symptoms presented by patients. The intervention of the respiratory therapist plays an important role in the management of patients diagnosed with community-acquired pneumonia, since the different procedures used are complemented by pharmacological treatment. The main basis of pharmacological treatment in patients diagnosed with community-acquired pneumonia are antibiotics, since these drugs help us fight this disease and in turn are complemented by respiratory therapy techniques.